THE INFLUENCE OF GOVERNMENT IDEOLOGY ON TURKISH MUSLIM DRESSING - Firstiyana Romadlon Ash Shidiqiyah; Siti Arafah (Arabic Literature Department, 2022)
This study aims to explain how government ideology has influenced the Turkish Muslim dress, particularly during the reign of Mustafa Kemal Pasha and Recep Tayyip Erdogan. This study used a historical method, which includes collecting and searching for sources and then processing the data to find facts. There were four stages in carrying out the historical approach, namely heuristics, criticism, interpretation, and historiography, while data collection is used literature review. The results indicated that the way Turkish Muslims dress has been influenced by government ideology. Meanwhile, during the time of Mustafa Kemal, who upheld the secularist ideology, Turkish people were forbidden from wearing head coverings, veils, Muslim clothing, and fez. Even the Turkish people were ordered to dress in a Western style, while during the time of Tayyip Erdogan, where he tried to transform Turkish secularism into a more moderate one, lifted some of the prohibitions during the Kemal era by allowing the Turkish people to wear headscarves, veils, fez and Muslim clothing.